2005
DOI: 10.1094/mpmi-18-0682
|View full text |Cite
|
Sign up to set email alerts
|

Quorum Sensing Regulates Exopolysaccharide Production, Motility, and Virulence in Pseudomonas syringae

Abstract: The N-acyl homoserine lactone (AHL)-mediated quorum-sensing system in the phytopathogen Pseudomonas syringae pv. syringae requires the AHL synthase AhlI and the regulator AhlR, and is additionally subject to regulation by AefR. The contribution of quorum sensing to the expression of a variety of traits expected to be involved in epiphytic fitness and virulence of P syringae were examined. Both an aefR- mutant and an ahlI- ahlR- double mutant, deficient in AHL production, were significantly impaired in alginate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
212
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(227 citation statements)
references
References 50 publications
12
212
1
1
Order By: Relevance
“…The ⌬psyI mutant showed the same level of swarming ability as the WT, although AHL-deficient mutants of P. syringae pv. syringae B728a exhibited high motility (25). Because this mutant is defective in both the ahlI and ahlR genes, which encode an AHL synthetic enzyme and a transactivator of AHL-responsive genes, the phenotype might be different from that caused by our single mutation of psyI in P. syringae pv.…”
Section: Vol 188 2006mentioning
confidence: 95%
See 2 more Smart Citations
“…The ⌬psyI mutant showed the same level of swarming ability as the WT, although AHL-deficient mutants of P. syringae pv. syringae B728a exhibited high motility (25). Because this mutant is defective in both the ahlI and ahlR genes, which encode an AHL synthetic enzyme and a transactivator of AHL-responsive genes, the phenotype might be different from that caused by our single mutation of psyI in P. syringae pv.…”
Section: Vol 188 2006mentioning
confidence: 95%
“…EPS production and tolerance to H 2 O 2 and antibiotics. Previous papers have reported that the production of EPS is regulated by quorum sensing and that an EPS-deficient mutant of P. syringae is hypersensitive to environmental stresses (7,17,25). To compare extracellular polysaccharide production on an MMMF plate with 1.5% agar after 48 h of incubation at 27°C, each mutant was scraped off and the amounts of extracellular polysaccharide and extracellular proteins as an internal control were quantified (Fig.…”
Section: Detection Of Ahls and Northern Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that a mutant of P. syringae deficient in EPS production had enhanced sensitivity to H 2 O 2 (Keith & Bender, 1999;Daniels et al, 2004;Quinones et al, 2005), and the Dorf3 mutant of P. syringae pv. tabaci 6605 had enhanced tolerance to H 2 O 2 and antibiotics due to the overexpression of EPS (Taguchi et al, 2006a).…”
Section: F Taguchi and Othersmentioning
confidence: 99%
“…aeruginosa possesses at least 2 well-defined acylhomoserine lactone (HSL)-based quorum-sensing systems, las and rhl, which control numerous virulence factor genes including lasA, lasB, and rhlA [1,2]. Each system comprises a transcriptional activator and an autoinducer synthase.…”
mentioning
confidence: 99%